Decorated or Undecorated: Analysis of the Early-Middle Neolithic Transition in Western Iberia Through the Ceramic’s Stylist Techniques and Decorative Motifs - Neves, César (2021)
In this article, we study the role played by pottery production in the transition from Early Neolithic to Middle Neolithic in Western Iberia (∼4500–3300 cal BC) based on a critical analysis of the available empirical data. We establish a chronological and cultural sequence for this period, regarding which the historical problematic is still poorly defined due to a lasting absence of scientific discussion about the long Neolithisation process. During the evolved Early Neolithic (∼5200–4500 cal BC), archeological record shows regional specificities and cultural identities in human groups occupying a vast territory. Pottery collections evidence the strong social importance of decorative grammars, marked by a wide variety of techniques and decorative patterns. In quantitative terms, decorated vessels largely prevail over undecorated vessels. However, in the following chrono-cultural phase, the Initial Middle Neolithic (∼4500–3700 cal BC), it starts an increasing prevalence of undecorated vessels over decorated. Decorative systems prefer the incision technique to impression (dominant in the Early Neolithic). Recurrent use of an incised motif called incised line below the rim. In this period, this type of decoration prevails in the set of decorated pottery and is found in different geographic contexts. This adds consistency to the interpretation according to which the same artifact collections are found in all settlements of the initial Middle Neolithic. Finally, by the time of the first-known Megalithic burials – Full Moment of the Middle Neolithic (3700–3300 cal BC) – the decorative grammars almost disappear from pottery sets, which became more “common” and missed some of their symbolic and social meaning. Undecorated vessels prevail even more strongly than in the previous period.